Famine, conflict, and political indifference. (10th May 2017) - Seal, Andrew; Hailey, Peter; Bailey, Rob; Maxwell, Daniel; Majid, Nisar
Abstract : Catastrophic combination for the people of Yemen, Somalia, South Sudan, and northern Nigeria